IMPACT OF MULTIPLE TAXATION ON BUSINESS SURVIVAL: A STUDY OF SMM WATER DIKKO, NIGER STATE - Masud, Abdullahi; Salisu, Ibrahim Yabagi; Alhaji, Umaru Abdulmalik; Adamu, Bawa Shuaibu; Isah, Ibrahim; Yusuf, Mohammed Abdullahi (Kashere Journal of Management Sciences, 2025)
This study is on the effect of multiple taxation business survival of SMM pure water in Dikko, Niger State, Nigeria. Over the years, small and medium scale enterprises have been an avenue of job creation and the empowerment of Nigeria’s citizen, providing about 50% of all jobs in Nigeria and also for local capital formation. However, the mortality rate of these small firms is very high. Among the factors responsible for these untimely close-ups are tax related issues, ranging from multiple taxations to enormous tax burdens. The study therefore examines the effect of multiple taxations on SMM survival. The study involved a survey research design with a population of 91 staff. The research sample size is 80 and a self administered questionnaire was used to collect data. The data was quantitatively analyzed with simple percentages and tested the research hypothesis with multiple regression model. Findings revealed that multiple taxation has negative effect on SMM’ survival and the relationship between SMM size and its ability to pay taxes is significant. We therefore recommends that government should come up with a uniform tax policies that will favour the development of SMEs in Nigeria and government should put into consideration the size of SMEs when setting tax policies.